A natureza nos empreendimentos imobiliários em Cuiabá-MT : o entorno do Parque Massairo Okamura - Barros, Rejane Cristina da Silva (2013)
This thesis aims to analyze how the developers and builders have sold the idea of nature to generate profits from land speculation, nature being represented here by Okamura Massairo State Park located in the, and in 2001 it was transformed into a nature reserve conservation unit sanctioned by Decree 3.345/01. Sought to meet the assessment that has nature - here represented by the green area of the park - by the visitors and residents of the same real estate projects located in the vicinity. Were put to debate the positives and negatives that piggybacking around the park cause the population, the environment and urban space. The choice of the area for the development of the present study is due to the park being a well implemented by the State of Mato Grosso; a public space whose environment has been speculated by appropriate and homebuilders who benefit by having their buildings and developments in nearby park, they start to be occupied by more affluent classes, since they can pay for their own recovery and the location in urban space further accentuating the process of segregation in the city.